Mongolian Ritual Texts in Manuscript Collections in the Czech Republic Part 1 - Srba, Ondřej (Masaryk University Press, 2022)
The present book is a critical edition of Mongolian ritual manuscripts preserved in Czech collections. It offers palaeographic descriptions and transcriptions for all the manuscripts, accompanied by English translations and selected facsimiles. The edition includes the majority of popular ritual text categories written in Classical Mongolian (mostly incense offering rituals) commonly circulating in the extramonastic milieu of premodern Mongolia: texts on fire-worship, White Old Man, Offering of the Fox, Geser Khan rituals, hunting rituals, while several texts related to cults of local deities, protection of livestock, as well as popular religious songs and individual prayers are appearing in the scholarly literature for the first time.